(untitled) (Revista Brasileira Multidisciplinar, 2024)
Forensic toxicological analyzes are valuable tools for tracking and confirming substances of forensic interest in different biological matrices. Drugs of abuse represent a worldwide public health problem, which can result in accidents and deaths. Conventionally, blood and urine are the main biological matrices for performing toxicological analyses. Oral fluid (OF) is nowadays one of the most commonly used alternative biological matrices for clinical and forensic drug testing. One of the interesting features of the OF is that the parent drug is often the predominant substance detected in the sample. In addition to the collection being simple and non-invasive. Different analytical methods for drug detection in alternative biological samples are available. This article aimed to summarize the main advantages of using OF for drug detection and to show the most used analytical methods in the last 5 years. For this, a search was carried out in the BVS, PubMed and Science Direct databases. The recognition of OF studies as an efficient and safe biological matrix for the detection of several drugs makes this matrix increasingly important in this scenario. However, tests using this biological matrix are still much smaller compared to blood and urine.